POWER REDUCTION IN MODERN VLSI CIRCUITS – A REVIEW - Ghosh, Debopam; Guha, Jyotirmoy; De, Arka; Mukherjee, Anirban (International Journal of Students' Research in Technology & Management, 2015)
This paper focuses on the importance of reducing power consumption by VLSI circuits using different power reduction techniques. In this paper, various sources of power dissipation in modern VLSI circuits along with various power reduction techniques as adopted in industry today are discussed.